Intraradicular Splinting with Endodontic Instrument of Horizontal Root Fracture - Ersan Çiçek; Neslihan Yılmaz; Mustafa Murat Koçak (Hindawi Limited, 2015)
Introduction. Root fractures, defined as fractures involving dentine, cementum, and pulpal and supportive tissues, constitute only 0.5-7% of all dental injuries. Horizontal root fractures are commonly observed in the maxillary anterior region and 75% of these fractures occur in the maxillary central incisors. Methods. A 14-year-old female patient was referred to our clinic three days after a traffic accident. In radiographic examination, the right maxillary central incisor was fractured horizontally in apical thirds. Initially, following local infiltrative anesthetics, the coronal fragment was repositioned and this was radiographically confirmed. Then the stabilization splint was applied and remained for three months. After three weeks, according to the results of the vitality tests, the right and left central incisors were nonvital. For the right central incisor, both the coronal and apical fragments were involved in the endodontic preparation. Results. For the right central tooth, both the coronal and apical root fragments were endodontically treated and obturated at a single visit with white mineral trioxide aggregate whilst the fragments were stabilized internally by insertion of a size 40 Hedstrom stainless-steel endodontic file into the canal. Conclusion. Four-year follow-up examination revealed satisfactory clinical and radiographic findings with hard tissue repair of the fracture line.